FACTORS AFFECTING TUBERCULOSIS (TB) PATIENT ADHERENCE TO ANTI-TUBERCULOSIS DRUG THERAPY IN SURABAYA - Dede Nasrullah; Uswatun Hasanah; Idham Choliq; Ira Purnamasari; Firman Firman; Islam Syaifurrahman; Vika Fitriyani (P3M Universitas 'Aisyiyah Surakarta, 2023)
Tuberculosis is one of the infectious diseases that causes many deaths in the world. One of the successes in reducing the death rate due to TB is with anti-tuberculosis treatment efforts. However, adherence to treatment is a serious problem because the results are still far from what is expected. The purpose of this study was to determine the level of adherence and what factors affect TB patients in treatment during the pandemic. This research was a descriptive analysis study with a cross-sectional approach. The number of samples was as high as 261 people. The measuring instrument used was the Medication Adherence Rating Scale (MARS). The validity and reliability showed that all questions were valid with a correlation value of > 0.396 and a Cronbach coefficient of 0.803. The results of the bivariate analysis showed that the factors influencing adherence to taking OAT in TB patients were age, education level, employment status, marital status, location of residence, and income level. Multiple logistic regression analysis showed the dominant factor having the most influence on compliance was the level of education. Respondents with a high school education level have a tendency to have a good compliance level of 22,077 times compared to respondents with a lower level of education.